Reformasi Pendidikan Pada Masa Jepang Meiji: Studi Tentang Peran Politik Kekuasaan Dalam Penerapan Pendidikan - Rustam, Ferry (Makara Human Behavior Studies in Asia, 2003)
The Meiji administration issued some new policies on education which were basically carried out socially by transforming the awareness of each citizen on the role of the state. The Japanese during the Tokugawa era were still bound by provincialism, whereas in the Meiji era they were obliged to have a national consciousness based on a nationalistic educational policy. The transformation of the provincial awareness to the nationalistic one is the most significant change carried out by the Meiji administration in the domain of education.